Exercise counteracts fatty liver disease in rats fed on fructose-rich diet - Botezelli, Jose D. [UNESP]; Mora, Rodrigo F. [UNESP]; Dalia, Rodrigo A. [UNESP]; Moura, Leandro P. [UNESP]; Cambri, Lucieli T. [UNESP]; Ghezzi, Ana C. [UNESP]; Voltarelli, Fabricio A.; Mello, Maria A. R. [UNESP] (Biomed Central Ltd., 2010)
Background: This study aimed to analyze the effects of exercise at the aerobic/anaerobic transition on the markers of non-alcoholic fatty liver disease (NAFLD), insulin sensitivity and the blood chemistry of rats kept on a fructose-rich diet.Methods: We separated 48 Wistar rats into two groups according to diet: a control group (balanced diet AIN-93 G) and a fructose-rich diet group (60% fructose). The animals were tested for maximal lactate-steady state (MLSS) in order to identify the aerobic/anaerobic metabolic transition during swimming exercises at 28 and 90 days of age. One third of the animals of each group were submitted to swimming training at an intensity equivalent to the individual MLSS for 1 hours/day, 5 days/week from 28 to 120 days (early protocol). Another third were submitted to the training from 90 to 120 days (late protocol), and the others remained sedentary. The main assays performed included an insulin tolerance test (ITT) and tests of serum alanine aminotransferase [ALT] and aspartate aminotransferase [AST] activities, serum triglyceride concentrations [TG] and liver total lipid concentrations.Results: The fructose-fed rats showed decreased insulin sensitivity, and the late-exercise training protocol counteracted this alteration. There was no difference between the groups in levels of serum ALT, whereas AST and liver lipids increased in the fructose-fed sedentary group when compared with the other groups. Serum triglycerides concentrations were higher in the fructose-fed trained groups when compared with the corresponding control group.Conclusions: The late-training protocol was effective in restoring insulin sensitivity to acceptable standards. Considering the markers here evaluated, both training protocols were successful in preventing the emergence of non-alcoholic fatty liver status disease.